EXAMINING SOCIAL ADJUSTMENT OF COLLEGE STUDENT-ATHLETES - Self, Mary Jo; Stowers, Nick Anthony (International Journal of Research -GRANTHAALAYAH, 2022)
The college experience is an important aspect of a student’s success in college. For student-athletes, there are additional pressures to maintain eligibility while competing in their sport. This study examines the social adjustment of student-athletes at the Division II level. The research explores differences that might exist in student-athletes and non-athletes in the area of social adjustment. In addition, differences in college adjustment between males and females are considered. For this study, 138 Student Adaptation to College Questionnaires (SACQ) were completed by student-athletes and non-athletes at two regional universities in Oklahoma. Only social adjustment scores were analyzed to identify the social adjustment of student-athletes. Findings revealed gender and athletic status were strongly associated with college adjustment. Implications and recommendations for future research are discussed.